A chemical weathering control on the delivery of particulate iron to the continental shelf. (1st September 2021) - Wei, Guang-Yi; Chen, Tianyu; Poulton, Simon W.; Lin, Yi-Bo; He, Tianchen; Shi, Xuefa; Chen, Jianfang; Li, Hongliang; Qiao, Shuqing; Liu, Jiahui; Li, Da; Ling, Hong-Fei
Abstract: The delivery of potentially reactive iron minerals to the marine environment exerts a major control on ocean and marine sediment biogeochemistry, including the preservation and burial of organic carbon. One aspect of the global iron cycle that has received little attention concerns the phase partitioning of iron in highly chemically-weathered sediments from (sub)tropical mountainous regions, where the sediment is commonly deposited directly onto adjacent continental margins. Here, we report the phase partitioning of particulate iron in surface seafloor sediments deposited from oxic bottom waters along the east coast of China, including the Bohai Sea, Yellow Sea and East China Sea, in addition to the continental shelf region adjacent to the (sub)tropical mountainous island of Hainan in the northern South China Sea. We document highly reactive (FeHR ) to total iron (FeT ) ratios for the Bohai Sea, Yellow Sea and East China Sea that are typical of global marine sediments deposited under oxic water column conditions. By contrast, FeHR /FeT ratios in Hainan offshore sediments are significantly elevated above normal oxic marine sediments. These Hainan offshore sediments display a strong positive correlation between FeHR /FeT ratios and the chemical index of alteration (CIA) weathering proxy, suggesting that the Fe speciation systematics are controlled by the intensity of chemical weathering. This observation is supported by additional geochemical data and Nd isotope analyses, which suggest a common source lithology for all the studied regions. The Hainan sediments thus document a specific scenario, whereby highly chemically weathered sediments from the mountainous Hainan region bypass the inner shore settings that commonly disproportionately trap Fe (oxyhydr)oxide minerals, depositing high concentrations of FeHR on the adjacent continental margin. Such enrichments likely aid in the preservation of organic carbon in marine sediments, suggesting that organic carbon preservation and burial may be enhanced by elevated FeHR in such settings. We also establish a set of essential criteria for potential recognition of chemical weathering-induced enrichments in FeHR /FeT ratios in ancient marine sediments.